Open versus laparoscopic appendicectomy: a prospective comparative study - Deshmukh, Santoshkumar N.; Pawar, Abhilash P. (International Surgery Journal, 2020)
Background: Open appendectomy has been the gold standard for the treatment of acute appendicitis since its introduction by Charles Mc Burney in 1889.The introduction of laparoscopic surgery has dramatically changed the field of surgery. Various studies showed conflicting results about the superiority of laparoscopic approach over open for treatment of acute appendicitis. Present study is conducted to determine any possible benefits of the laparoscopic approach over open surgery. Methods: The study was conducted in Dr. V. M. Government Medical College and hospital located in Solapur (Maharashtra) from September 2017 to September 2019. It is a prospective comparative study. Patients were randomly divided into 2 groups alternately where group A and B were operated by conventional and laparoscopic techniques respectively and their outcomes were compared. Results: Mean age of patients in open and laparoscopic appendicectomy group was 29.67 years and 31 years respectively. Post-operative pain, wound infection and hospital stay was significantly more in open group as compared to laparoscopic group (p<0.05). Conclusions: From the results of our study we conclude that laparoscopic appendicectomy has superior results as compared to open appendicectomy.